2017
DOI: 10.1007/s00606-017-1422-y
|View full text |Cite
|
Sign up to set email alerts
|

Notonuphar antarctica, an extinct water lily (Nymphaeales) from the Eocene of Antarctica

Abstract: A new genus and species, Notonuphar antarctica, is described from the Eocene of Seymour (Marambio)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Some fossil marsupials show a similar pattern to this (Case et al ., 2005; Goin et al ., 2006). Concerning this biotic exchange hypothesis, fossil plants have been discussed to a limited degree (Wilf et al ., 2013) with some lineages showing a North America to South America–Antarctica migration during the Cretaceous and Paleogene, including Regnellidium (Batten et al ., 2011; Cúneo et al ., 2013) and some nymphaleans (Gandolfo & Cuneo, 2005; Friis et al ., 2017). Poole et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some fossil marsupials show a similar pattern to this (Case et al ., 2005; Goin et al ., 2006). Concerning this biotic exchange hypothesis, fossil plants have been discussed to a limited degree (Wilf et al ., 2013) with some lineages showing a North America to South America–Antarctica migration during the Cretaceous and Paleogene, including Regnellidium (Batten et al ., 2011; Cúneo et al ., 2013) and some nymphaleans (Gandolfo & Cuneo, 2005; Friis et al ., 2017). Poole et al .…”
Section: Discussionmentioning
confidence: 99%
“…hypothesis, fossil plants have been discussed to a limited degree(Wilf et al, 2013) with some lineages showing a North America to South America-Antarctica migration during the Cretaceous and Paleogene, including Regnellidium(Batten et al, 2011;C uneo et al, 2013) and some nymphaleans(Gandolfo & Cuneo, 2005;Friis et al, 2017). Poole et al (2000b) reported Sassafrasoxylon Brezinov a et S€ uss from Late Cretaceous deposits in Antarctica and cautiously discussed that Sassafras J. Presl, which today is restricted to the Northern Hemisphere, may have had a Gondwanan origin.…”
mentioning
confidence: 99%
“…In addition to the TELM stratigraphy convention, Marenssi et al (1998) introduced five erosionally based allomembers for the La Meseta and Submeseta Fms., which roughly correspond to TELMs as reported in Table 1. Further, Montes et al (2013) divided the Acantilados Allomember into Acantilados I (referred to as Level 32 in some instances) with minor Table 1 Description of TELM Biostratigraphy, Faunal Content, Sedimentology, and Allomembers Compiled From Published Research to Date (Bomfleur et al, 2015;Buono et al, 2016;Friis et al, 2017;Ivany et al, 2008;Kriwet et al, 2016;Marramá et al, 2018;McLoughlin et al, 2016;Montes et al, 2013;Sadler, 1988;Schwarzhans et al, 2017;Stilwell & Zinsmeister, 1992…”
Section: Geologic Settingmentioning
confidence: 99%
“…; Friis et al . ) that imply nearshore deposition. Although the La Meseta Formation has traditionally been assigned ages ranging from early Eocene to ?earliest Oligocene (Ivany et al .…”
Section: Geological Backgroundmentioning
confidence: 99%